An overview of radioisotope separation technologies for development of 188W/188Re radionuclide generators providing 188Re to meet future research and clinical demands. Issue 49 (30th May 2015) - Dash, Ashutosh; Knapp Jr, F. F. (Russ)
<x xml:space="preserve">Abstract</x> Separation technologies for 188W/188Re radionuclide generators.